State-changing processes for ions in cold traps: LiH− molecules colliding with He as a buffer gas. (4th November 2016) - González-Sánchez, L; Gianturco, F A; Wester, R
Abstract: We report in the present study a quantum analysis of the collisional dynamics involving a negative ion, LiH − in its 2 Σ + ground electronic state, and He as a buffer gas in the environment of cold ion traps. The work focuses on the evaluation of the internal cooling collisional rates, treating both the anion's rotational quantum numbers and the spin-changing processes. The calculations are carried out over a range of energies capable of yielding the corresponding rates for state-changing events over a rather broad interval of temperatures, thus covering those usually reached in the cold traps experiments and even beyond to lower temperatures.